THE INFLUENCE OF COMMUNICATION AND NON-PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Panjaitan, Saur; Hidayat, Rahmat (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to examine the Influence of Communication and Non-Physical Work Environment on Employee Performance with Job Satisfaction as an Intervening Variable at PT Minebea AccessSolutions Indonesia Plant 2 (Case Study in the Assembly Department). This type of research is quantitative research. The number of samples is 121 employees working at PT Minebea AccessSolutions Indonesia Plant 2. The data used in this study are primary and secondary data, namely by distributing questionnaires and via google form to employees of PT Minebea AccessSolutions Indonesia Plant 2. This study uses the Lisrel 8.8 data processing application. The results of this study are (1) Communication does not affect Job Satisfaction, (2) Non-Physical Work Environment affects Job Satisfaction, (3) Communication and Non-Physical Work Environment simultaneously affect Job Satisfaction, (4) Communication affects Employee Performance, (5) Non-Physical Work Environment does not affect Employee Performance, (6) Job Satisfaction does not affect Employee Performance, and (7) Communication, Non-Physical Work Environment, and Job Satisfaction simultaneously affect Employee Performance.